Quantitative and qualitative evaluation of saffron (Crocus sativus L.) for genetic variability, character association and path analysis: Genetic variability, character association and path analysis in saffron - Irfan, Mohammad; Rahid, Uzma; Nasseer, Sabeena; Bhat, M Ashraf; Dar, Z A; Wani, M Altaf; Rasool, Shahid; Khan, M H; Wani, Rayees A (Journal of Spices and Aromatic Crops, 2023)
Different accessions of saffron were studied to analyze genetic diversity and heritable component of variation in yield and yield related traits. Dry pistil weight, fresh pistil weight, fresh flower weight corm-1 line-1, number of flowers corm-1 line-1, and big corm index, all had high genotypic coefficient of variation, heritability and genetic advance. The traits included in the selection scheme, correlation among traits (floral and agronomic) are important as varieties must have high yield associated with exemplary quality parameters. At both phenotypic and genotypic levels, the association was found significant among the traits. Stigma length and fresh flower weight had strong direct effect with respect to dry pistil weight followed by number of flowers corm-1 line-1, fresh pistil weight and big corm index. Therefore, these parameters can be taken as criteria for selection.